2020
DOI: 10.1038/s41533-020-00203-x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of inhaler use at home with a smartphone video application in a pilot study

Abstract: Inhalation therapy is the basis of the pharmacological management of asthma and COPD. Most patients are trained on the correct use of inhalers by health professionals but after that do patients continue to take them correctly at home remains largely unknown. Video recording of the inhalation technique using a smartphone can be used to evaluate the inhaler technique at home. Through this pilot study, we aimed to understand whether inhaler training given to patients in the outpatient clinic translates into good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The poor inhaler technique identified in this study is a global issue with little improvement over the past 40 years 49 . Video applications used to monitor patients' inhaler techniques at home have found that errors in technique start appearing as early as the first day after training 50 . WeChat might be a useful tool for improving inhaler technique.…”
Section: Discussionmentioning
confidence: 99%
“…The poor inhaler technique identified in this study is a global issue with little improvement over the past 40 years 49 . Video applications used to monitor patients' inhaler techniques at home have found that errors in technique start appearing as early as the first day after training 50 . WeChat might be a useful tool for improving inhaler technique.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Some of the key features that participants in this study noted for the m-health asthma care application: medication tracking, symptom tracking, video education of inhaler technique, and home assessment of inhaler technique, have been successfully utilized in other m-health applications to improve asthmarelated outcomes. [31][32][33] In addition, a prior study identified that parents of children who receive school-based asthma care valued communication from the school and using a mobile application for asthma care may achieve this goal. 34 Finally, clinicians have previously noted similar concerns to implementation of mobile health regarding access to technology and smart phones.…”
Section: Discussionmentioning
confidence: 99%
“…Having been trained to mastery in the clinic, inhaler technique was seen to drop steadily over time (days 1, 7, 14, and 28). However, the method of remotely observing inhaler technique via videos provided a means to intervene to correct and prevent inhaler technique errors ( 20 ).…”
Section: Video Directly Observed Therapymentioning
confidence: 99%